Data-Driven Bioinformatics is a Popular but Wrong and Misleading Attempt to Assess the Information-Handling Abilities of Natural Biological Systems - Diamant, Emanuel (Transactions on Engineering and Computing Sciences, 2023)
It is generally agreed and accepted that Information is an indispensable part of our modern everyday life. But that does not mean that a generally agreed and accepted understanding of what information is or may be does exist in the general public or in the specific scientific communities. Norbert Wiener’s dictum “Information is information, not matter or energy” is not a definition, but expresses pretty well the existing ambiguity and embarrassment about the discoursed matters.